Taxonomic study of the genus Punctulata Wang (Lepidoptera: Autostichidae) from China, with descriptions of two new species - Tao, Zhulin; Wang, Shuxia (Zootaxa, 2021)
The genus Punctulata Wang, 2006 is transferred from Oecophoridae to Autostichidae based on morphological characters and molecular data. Punctulata guangxiensis sp. nov. and P. novipalliptera sp. nov. are described as new based on the specimens collected in China. The females of P. palliptera Wang, 2006 and P. trunciformis Wang, 2006 are described for the first time. Images of male adults and male and female genitalia are provided for all the six Punctulata species along with a key to separate its species and a map showing their distribution.